SOSIALISASI 3 DOSA BESAR DALAM PENDIDIKAN UNTUK MENANAMKAN NILAI KARAKTER BAGI SISWA/I SMK KARYA NASIONAL, KAB. KUNINGAN JAWA BARAT - Niantoro Sutrisno; Ahmad Saepudin; Euis Winarti; Susanto; Jalaludin, Jalaludin (JURNAL ABDIMAS PLJ, 2024)
This study discusses the 3 big sins of education that many students in indonesia do not yet know what the 3 big sins are in the world of  education. The aim of this activicy is to analyze and find ways to prevent the 3 major sins in the education of student participants at SMK  Karya Nasional. This activity method  uses a lecture (presentation) method to provide material counseling to the participants. This socialization activity aims to help students understand their understanding of the 3 major sins and their negative impacts, as well as offering practical solutions to support students perfect personality development. From the result obtained, students can learn from the consequences of bullying, sexual violence and intolerance by preventing it and even eliminating it. Apart from that, efforts must be made by schools, namely by providing a special place to provide students with learning material about friendship etiquette, learning etiquette, as well as material about the negative impacts of bullying and sexual violence